Hydraulic modeling and experimental study of three heat sources and three rings heating networks. (2017) - Zhou, Shoujun; Gong, Pu; Wang, Tao; Li, Haiming
Abstract: For the further research on the hydraulic characteristics of multi-source and multi-ring heating network polycyclic, this paper based on the fluid network analysis, the hydraulic intersection user virtual segmentation, at the ends of common pipe set virtual users or virtual heat source modeling method, the hydraulic simulation model of three heat sources and three rings of a heating pipe network is established by using MATLAB platform. Based on the experimental platform of the multi-source heat supply network, the three heat sources and rings ideal working conditions and the variation of the two working conditions are simulated and experimentally studied. The results show that under the 3 different conditions, the maximum absolute value of relative error of simulation data and the experimental data were 1.30%, 1.26% and 1.09%, to verify the validity of the simulation method proposed in this paper and the simulation model and the accuracy of.